2020
DOI: 10.31933/dijdbm.v1i2.134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Work Environment and Motivation on Workload and Its Implications on Employee Performance Pt. PLN (Persero) Up3 Kebon Jeruk

Abstract: This study aims to determine and clarify the effect of work environment and work motivation for workload and its implementation on employee performance. Respondents 67 employees (entire population). Data collection is done through interviews and questionnaires. Data were analyzed using path analysis (SmartPls 3.0 software) and correlation matrix between dimensions (SmartPls 3.0 software). The results showed that: (1) Work Environment and Motivation both partially and simultaneously affect Employee Performance;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
1
0
2
Order By: Relevance
“…This finding is in line with the results of research conducted by Jahari (2019), Parulian et al (2020), Rusmiati et al (2021) which also showed that workload has a positive and significant effect on employee performance in several companies in Indonesia. Thus, it can be asserted that the role of Workload in influencing employee performance is a consistent phenomenon in the context of various immigration offices.…”
Section: The Effect Of Workload On Passport Service Performancesupporting
confidence: 90%
“…This finding is in line with the results of research conducted by Jahari (2019), Parulian et al (2020), Rusmiati et al (2021) which also showed that workload has a positive and significant effect on employee performance in several companies in Indonesia. Thus, it can be asserted that the role of Workload in influencing employee performance is a consistent phenomenon in the context of various immigration offices.…”
Section: The Effect Of Workload On Passport Service Performancesupporting
confidence: 90%
“…Research by Al-Amin (2017), Afiani et al, (2019), Cahyani & Siswanto (2019), Tasnim & Yulihasri (2020), and Hardiyanti et al, (2022 states that transformational leadership has a positive and significant effect on employee performance , but it is different from the research results of Rafia et al, (2020) which stated that transformational leadership had a positive but not significant effect on employee performance. The research results of Ardi et al, (2017), Arifin et al, (2021), Maria et al, (2021) Pulungan & Rivai (2021) and Wibowo & Priyono (2022) state that self-efficacy has a positive and significant effect on employee performance, however, this is different from the research results of Permata Sari & Candra (2020) which stated that self-efficacy has a positive but not significant effect on employee performance.…”
Section: Introductionmentioning
confidence: 89%
“…Hasil yang positif dan signifikan memperlihatkan bahwa dorongan yang diberikan kepada karyawan jika semakin tinggi, maka kinerja karyawan juga akan meningkat. Berdasarkan temuan di atas, studi ini dikuatkan oleh penelitian sebelumnya oleh Yasin & Mahfudiyanto (2018), Parulian & Sutawijaya (2020) dan Riandi et al (2021) yang menyimpulkan dorongan berdampak positif tehadap prestasi kerja. Jadi, medorongan karyawan menjadi sangat penting dalam perusahaan karena akan membantu menyelesaikan setiap problem dan kejenuhan dalam bekerja.…”
Section: H3unclassified
“…Kinerja secara definisi umum diistilahkan sebagai keberhasilan seseorang dalam melaksanakan suatu pekerjaan (Parulian & Sutawijaya, 2020). Kinerja mencakup kualitas dan kuantitas keluaran dan keandalan di tempat kerja.…”
unclassified